Cooperation as a Result of Learning with Aspiration Levels - Jörg Oechssler (University of Bonn, Bonn Graduate School of Economics (BGSE), 2001)
It is shown that a win-stay, lose-hift behavior rule with endogenous aspiration levels yields cooperation in a certain class of games. The aspiration level in each round equals the current population average. The class of games includes the prisoner's dilemma and Cournot oligopoly and thus yields an explanation for cooperation and collusion.
Keywords: C72; L13; 330; cooperation